Can Informal Water Vendors Deliver on the Promise of A Human Right to Water? Results From Cochabamba, Bolivia. (March 2016) - Wutich, Amber; Beresford, Melissa; Carvajal, Cinthia
Summary: We examine the role of informal water vendors in the urban poor's efforts to secure safe and affordable water in the squatter settlements of Cochabamba, Bolivia. Using an economic justice framework, we evaluate (1) how informal water markets operate, (2) differences in client and vendor perceptions of distributive, procedural, and interactional (in)justice, and (3) how cooperation among water vendors impedes or assists in achieving justice in water delivery. The research includes a comparative institutional analysis of three key data sets: long-term participant-observation in water-scarce squatter settlements; interviews with 12 water vendors; and interviews with 41 clients from 23 squatter settlements. We find that informal water vendors organize themselves to safeguard distributive justice (e.g., fair pricing, good water quality), but clients are distressed by procedural and interactional injustices (e.g., unreliable and inequitable service). Our research also shows that unionized vendors are more effective than non-unionized vendors in creating and enforcing rules that advance distributive, procedural, and interactional justice. We make concrete recommendations for improving justice in informal water markets, including a larger role for unions and community consultation. We conclude that, despite challenges, the informal economy may play an important role in advancing the human right to water.